Computer-Based Generation of Learner-Sensitive Feedback to Argumentative Learner Texts - Kilsbach, Sebastian; Michel, Nadine (Proceedings of the Tenth Conference of the International Society for the Study of Argumentation)
What is learner-sensitive feedback to argumentative learner texts when it is to be issued computer- based? Learning stages are difficult to quantify. The paper provides insight into the history of research since the 1980s and a preview of what this automated feedback might look like. These questions are embedded in a research project at the Universities of Paderborn and Hannover, Germany, from which a software (project name ArgSchool) emerges that will provide such feedback.
Keywords: AI; argumentation mining; discourse history; (automated; learner-sensitive) feedback

Überlegtes und überlegenes Reiten oder Beobachtungen des Affekteinsatzes: Montaigne ‚Des coches' (1588) - Steigerwald, Jörn (Einsatz der Affekte. Zum Schrifttum der europäischen Expansion)

Johann Elias Schlegels Revision der Tyrannentragödie: Die ‚Lucretia' - Steigerwald, Jörn (Johann Elias Schlegel und das Theater. Zwischen Revision und Reform)

Robert Garniers Bradamante (1582/1584) oder: wie die Tragikomödie die französische Bühne erneuert - Steigerwald, Jörn (Erneuerungen und Positionierungen der Tragödie in der frühmodernen Romania)

Putting algorithmic bias on top of the agenda in the discussions on autonomous weapons systems - Bhila, Ishmael (Digital War)
Abstract Biases in artificial intelligence have been flagged in academic and policy literature for years. Autonomous weapons systems—defined as weapons that use sensors and algorithms to select, track, target, and engage targets without human intervention—have the potential to mirror systems of societal inequality which reproduce algorithmic bias. This article argues that the problem of engrained algorithmic bias poses a greater challenge to autonomous weapons systems developers than most other risks discussed in the Group of Governmental Experts on Lethal Autonomous Weapons Systems (GGE on LAWS), which should be reflected in the outcome documents of these discussions. This is mainly because it takes longer to rectify a discriminatory algorithm than it does to issue an apology for a mistake that occurs occasionally. Highly militarised states have controlled both the discussions and their outcomes, which have focused on issues that are pertinent to them while ignoring what is existential for the rest of the world. Various calls from civil society, researchers, and smaller states for a legally binding instrument to regulate the development and use of autonomous weapons systems have always included the call for recognising algorithmic bias in autonomous weapons, which has not been reflected in discussion outcomes. This paper argues that any ethical framework developed for the regulation of autonomous weapons systems should, in detail, ensure that the development and use of autonomous weapons systems do not prejudice against vulnerable sections of (global) society.

Autonomous Vehicles: Threats, Risks, and Opportunities - Bhila, Ishmael; Lee, Peter; Wakefield, Alison

Biased Voluntary Nutri-Score Labeling - Schnedler, Wendelin; Vigano, Antonia (The B.E. Journal of Economic Analysis & Policy)
Food labels are supposed to quickly inform consumers about the nutritional values of products. We provide evidence that in a system where labels are voluntary, they are systematically distorted. The probability of finding a label on a product of the category with the highest nutritional value is 51 percentage points larger than in the lowest category.

Wieso, weshalb, warum – Fachkulturen und -praktiken mit der Unterstützung von studentischen Culture Fellows entdecken - Brandt, Eileen; Schmöckel, Sabrina (bwp@ Berufs- und Wirtschaftspädagogik Spezial)

Becoming Kathrine Talbot: A Jewish Refugee and the Novelist She Invented - Ribbat, Christoph

Sicherheit bei Großveranstaltungen – Mobilitätsverhalten und Personenströme im Fokus - Schultz, Andreas Maximilian; Dotzki, Fabian; Eisenbach, Thomas; Mozgova, Iryna (Next Chapter in Mobility)

Elionor of Sicily, 1325–1375: A Mediterranean Queen of Two Worlds - Foerster, Anne (Speculum)

Rezension zu Timo Güzelmansur/Tobias Specker/ChristianTrenk (Hrsg.): Glaube/Unglaube. Islamische und christliche Deutungen - Kokew, Stephan Matthias (Apokalypse. Theologisch-praktische Quartalschrift 2/2024)

Jamāl ad-Dīn al-Qāsimī - Kokew, Stephan Matthias (Handbook of Qurʾānic Hermeneutics. Volume 4: Qurʾānic Hermeneutics in the 19th and 20th Century)

Facetten von ḏimma. Altbekanntes und Neues - Kokew, Stephan Matthias (Cibedo-Beiträge zum Gespräch zwischen Christen und Muslimen)

Cai, Hong (2022): Bedarfsanalysen für einen berufsbegleitenden Fremdsprachenunterricht am Beispiel von Deutsch als Fremdsprache. München: IUDICIUM Verlag. ISBN: 978-3-86205-625-5. 382 Seiten. 48,00 €. - Prikoszovits, Matthias (Zeitschrift für Interkulturellen Fremdsprachenunterricht (ZIF))

Lebensweltorientierung in der (a)synchronen WhatsApp-Interaktion zwischen brasilianischen und jordanischen DaF-Lernenden. Themenwechsel und Themenverschiebungen in the wild. - Prikoszovits, Matthias (Zeitschrift für Interaktionsforschung in DaFZ)

Förderung der sozialen Partizipation von Kindern in der Primarstufe – Befunde aus einer Interventionsstudie. Vortrag auf der Tagung der Österreichischen Gesellschaft für Forschung und Entwicklung im Bildungswesen (ÖFEB). Thema: „Diversität diskursiv. Bildungswissenschaftliche Zugänge und pädagogische Perspektiven“ - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Sources of pre-service teachers' self-efficacy beliefs concerning inclusive teaching. Oral Paper Presentation. EARLI SIG 15 Biennial Conference 2024 ‘Special Educational Needs’. “Neurodiversity in Education: Research and Practice”. - Görel, Gamze; Franzen, Katja; Hellmich, Frank

Effects of an intervention on students’ attitudes towards peers with special educational needs. Poster Presentation. EARLI SIG 15 Biennial Conference 2024 ‘Special Educational Needs’. “Neurodiversity in Education: Research and Practice” - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Fostering students’ attitudes towards peers with special educational needs – Findings from a social participation intervention. Porto International Conference on Research in Education (ICRE) 2024 - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank